2000
DOI: 10.2105/ajph.90.11.1746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health insurance and race on colorectal cancer treatments and outcomes

Abstract: OBJECTIVES: We hypothesized that health insurance payer and race might influence the care and outcomes of patients with colorectal cancer. METHODS: We examined treatments received for all incident cases of colorectal cancer occurring in Florida in 1994 (n = 9551), using state tumor registry data. We also estimated the adjusted risk of death (through 1997), using proportional hazards regression analysis controlling for other predictors of mortality. RESULTS: Treatments received by patients varied considerably a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(49 citation statements)
references
References 62 publications
(59 reference statements)
6
43
0
Order By: Relevance
“…U.S. Census data published in 2012 showed that 15.4%, or 48 million Americans, went uncovered by health insurance, and Medicaid covered 16.4%, or 51 million Americans (DeNavas-Walt, US census bureau, 2013). Lack of insurance coverage has been associated with worse survival and postoperative complications in critical illness (21), trauma (22), breast cancer (23), uterine cancer (24), colorectal cancer (25, 26), prostate cancer (27), diffuse large cell lymphoma (28), head and neck cancer (29), and lung cancer (30). Attributable causes for worse clinical outcomes in uninsured Americans include more advanced disease at time of diagnosis, fewer diagnostic tests performed, and decreased healthcare literacy (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…U.S. Census data published in 2012 showed that 15.4%, or 48 million Americans, went uncovered by health insurance, and Medicaid covered 16.4%, or 51 million Americans (DeNavas-Walt, US census bureau, 2013). Lack of insurance coverage has been associated with worse survival and postoperative complications in critical illness (21), trauma (22), breast cancer (23), uterine cancer (24), colorectal cancer (25, 26), prostate cancer (27), diffuse large cell lymphoma (28), head and neck cancer (29), and lung cancer (30). Attributable causes for worse clinical outcomes in uninsured Americans include more advanced disease at time of diagnosis, fewer diagnostic tests performed, and decreased healthcare literacy (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…1417 The findings are also important, considering that the uninsured are often reluctant to seek care due to concerns about cost and, as a result, often have worse health outcomes. 6,14,15,29–31 With the increase in Medicaid coverage, perhaps more patients in New York were willing to seek out and receive specialty care. Similar results were reported by Hanchate and colleagues, who reported that use of inpatient surgical procedures increased after institution of universal coverage in Massachusetts.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is of particular interest because Medicaid beneficiaries already encounter substantial difficulties in accessing specialty services. 6,1418 We used the largest natural experiment of Medicaid-only expansion, in New York State in 2001, 19,20 to evaluate the effects of this policy change on use of inpatient plastic and reconstructive surgery procedures by Medicaid beneficiaries. We also assessed use by patients without health insurance coverage (ie, uninsured) to understand if expanding Medicaid resulted in reduced access to previously available care for those who remained uninsured.…”
mentioning
confidence: 99%
“…Whether suffering acute coronary syndrome or breast or colorectal cancers, uninsured patients have been found to present at later more severe stages of illness and disease often necessitating more resource-intensive care and suffering worse outcomes (47-50). Review of hospital and ICU service utilization in Massachusetts following a decrease in the uninsured population rate from 9.3% to 5.1% found no significant change in ICU admission rates or mortality (51).…”
Section: Discussionmentioning
confidence: 99%